The Properties of Wet Blue Added Crude Enzyme from Rhizopus oligosporus in the Acid Bating Process - A. W. Nugraha; O. Suparno; N. S. Indrasti; Hoerudin (Faculty of Animal Science, Bogor Agricultural University, 2022)
Bating is one of the processes in leather production. This process is generally performed under slightly alkaline conditions, but it can also be done under acidic conditions. Rhizopus oligosporus is categorized as a microorganism that can synthesize acidic enzymes optimally in acidic conditions. This study aimed to evaluate the effect of the bating process using acid protease from R. oligosporus on the leather qualities tanned by chromium sulfate. The study used a completely randomized design where crude enzyme activity (0, 2.5, 5, 7.5, and 10 U mL-1) was a single treatment as an experimental design. Data were analyzed using ANOVA and furtherly tested using Duncan. The results show that the protease synthesized from R. oligosporus is potential to be used as a bating agent. The treatment with 2.5 U mL-1 activity was the best treatment in this study to improve leather (wet blue) properties like shrinkage temperature, ash content, and chrome oxide content. The quality of wet blue produced was better than that produced with conventional treatments. It can be concluded that the enzyme activity of 2.5 U mL-1 could be used as a bating-agent alternative in the acid bating stage.